INFLUENCE OF CULTIVAR AND DENSITY ON PLANT GROWTH AND PRODUCTION OF SWISS CHARD (Beta vulgaris, subsp. cicla), IN WESTERN ROMANIA - Alexandru Ioan Apahidean; Mihai Cărbunar; Mariana Bei; Rodica Sima; Orsolya Borsai (Agricultura)
In Romania, Swiss chard is a less cultivated species, being present in some areas of Transylvania, on small surfaces. This research paper presents the results regarding the growth and the productions of Swiss chard, quantitative and qualitative, obtained in the specific conditions of western Romania. Purpose of the research was to establish how some Swiss chard cultivars behave, under different density conditions. Experiment was bifactorial, (3x4 type), with 12 experimental variants. Comparative crops were carried out in the summer-autumn period, with differences in growth of Swiss chard plants (plant height, petiole length and thickness) as well as in production, at different densities. For some experimental variants, yields obtained were over 50 t/ha, being comparable to those obtained and mentioned in the literature. Content of mangold leaves in dry matter as well as in vitamin C was also measured, the results being comparable to those obtained in other growing conditions in Europe.